Données linguistiques, données sociolinguistiques: le traitement labovien du vernaculaire africain-américain - Bourquin, Céline (My University, 2004)
From 1965 to 1968, William Labov conducted an empirical research into AfricanAmerican Vernacular English in South Central Harlem. This paper's main aim is to reflect on his method. Four "phases" are distinguished. The first one is equivalent to data production, it has to do with procedures used for reaching African American Vernacular English. The second one is about the analysis of specifically linguistic data, while the object of the third and the fourth "phases" is the data analysis from ethnographic observation.